Design and Application of Automatic Preprocessing and Information Extraction of Enteromorpha Based on Remote Sensing Images - ZHANG Haorui; CHANG Junfang; FU Hongtao; WU Yuhua; CHEN Jian (Haiyang Kaifa yu guanli)
This paper proposes a method of automatic preprocessing and information extraction of satellite remote sensing image data based on ENVI and ArcGIS, which is applied to satellite remote sensing monitoring of enteromorpha in the Yellow Sea. According to the characteristics of remote sensing data from different satellites, ENVI is customized to carry out geometric correction, orthographic correction, mosaic, clipping, NDVI calculation and other steps to achieve automatic preprocessing of medium and high resolution of multi-spectral satellite remote sensing data. At the same time, ArcGIS software was used to vectorize raster data and quantize the scale of enteromorpha, which provided high-quality satellite remote sensing image processing results for monitoring personnels. In the practical work, the problem of complicated and time-consuming operation process of remote sensing image preprocessing of enteromorpha in the Yellow Sea was solved. The results of experiments on remote sensing images of enteromorpha in the Yellow Sea in 2023 show that the method has good performance in automatic preprocessing of multi-source satellite remote sensing data and enteromorpha information extraction, and the processing time is shortened, which can meet the requirements of practical applications.